In Cultural Stereotypes Hungarian Business Professionals Trust: Myth or Reality? - Julia SZOKE (Communications of International Proceedings, 2021)
Stereotypes are generalizations about a given culture or nation, therefore, they are considered to be less relevant or important. Yet, stereotypes are parts of our lives, which virtually makes it impossible to not face with them, not consider them or even not reflect them in our behavior. Therefore, the present paper aims to investigate the degree to which Hungarian business professionals believe and trust stereotypes and also act based upon them in their cross-cultural relationships. Thus, the paper looks into the theoretical background to stereotypes as well as their relation to trust, and then presents the results of a two-phase empirical research, with a special emphasis on those of the qualitative phase. The results indicate that stereotypes, both positive and negative ones, have an influence on the respondent business professionals to some extent. The paper concludes that the effect of stereotypes is manifested indirectly, mainly through changed behavior and attitude towards the foreign partner, however, it must be stressed that this change is not necessarily negative. The findings are believed to contribute to a better understanding of business professionals’ cross-cultural behavior, and also to be useful for business professionals.
Keywords: Behavior; Cross-Cultural Relationships; Stereotype; Trust.